Follow–up beyond 1 month after autologous CAR T cell therapy - Ribeiro, Andreza Alice Feitosa (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2022)
The incidence of medium-term and long-term adverse events are critical factors determining the utility of CAR T-cell therapy and research of risk factors and timeline of late effects will be critical for optimal survivorship care. The most commonly reported toxicities during long-term follow-up after anti-CD19 CAR T-cell therapy are decreased blood B-cell counts, hypogammaglobulinemia, prolonged cytopenias and infections. Common determinants of late toxicities are age, underlying tumor type, previous therapy and CAR construct. Here we will provide some recommendations for patient monitoring during medium-term and long-term follow-up and management of the late adverse effects.